Application of fuzzy neural network model and current-voltage analysis of biologically active points for prediction post-surgery risks. Issue 13 (3rd October 2021) - Shatalova, Olga; Filist, Sergey; Korenevskiy, Nikolay; Taha Al-kasasbeh, Riad; Shaqadan, Ashraf; Protasova, Zeinab; Ilyash, Maksim; Rybochkin, Anatoly
Abstract: The work investigates neural network model for prediction of post-surgical treatment risks. The descriptors of the risk classifiers are formed on the basis of the analysis of the current-voltage characteristics of one, two and three biologically active points. The training and verification samples were formed by examining 120 patients with a diagnosis of benign prostatic hyperplasia. Of these, 62 patients were successfully operated on (class C1), 30 had various complications after surgery (class C2), 28 patients required additional treatment (class C3). The constructed classifiers showed a high quality of predicting critical conditions during surgical treatment.